2020
DOI: 10.18502/ijph.v48i10.3495
|View full text |Cite
|
Sign up to set email alerts
|

Home Food Safety Practice and Household Food Insecurity: A Structural Equation Modeling Approach

Abstract: Background: Food safety and food security are interrelated concepts with a profound impact on the quality of human life. The current study, for the first time, was set to identify associations between home food safety practice and household food insecurity a structural equation modeling approach. Methods: In this cross-sectional study, urban households were selected from among 10 health centers of five districts of Tehran, Iran (2015). The following questionnaires were completed: socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Participants with food insecurity had significantly greater concerns about COVID-19 transmission through food and engaged in more unsafe food handling practices in attempts to prevent transmission. These findings are consistent with results from a previous study that found greater food security was associated with less engagement with food safety practices prior to the pandemic ( 9 ) . Most COVID-19–related food safety studies examined sociodemographic factors associated with food handling practices ( 41 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Participants with food insecurity had significantly greater concerns about COVID-19 transmission through food and engaged in more unsafe food handling practices in attempts to prevent transmission. These findings are consistent with results from a previous study that found greater food security was associated with less engagement with food safety practices prior to the pandemic ( 9 ) . Most COVID-19–related food safety studies examined sociodemographic factors associated with food handling practices ( 41 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Penelitian yang dilakukan di Iran (n= 630) menunjukkan 29.5% ibu memiliki praktik keamanan pangan yang masih kurang baik, 33% masih dapat diterima dan hanya 37.5% yang sudah baik (Esfarjani et al 2019). Sementara penelitian yang dilakukan pada penjamah pangan di Filipina saat pandemi menunjukkan bahwa penjamah pangan belum memenuhi standar praktik keamanan pangan yang baik terutama dalam hal penyiapan bahan pangan, kontaminasi silang, proses memasak dan kebersihan yang kurang baik (Limon 2021).…”
Section: Praktik Keamanan Panganunclassified
“…Structural Equation Model (SEM) has been widely used in food safety analysis [16,17]. With SEM analysis, it can be seen which latent variables affect the food safety behavioural intentions of food handlers, as well as provide a measure of the magnitude of the resulting effect.…”
Section: Introductionmentioning
confidence: 99%